THE DYNAMICS OF REPRESSIVE HABITUS LAWS: ETHNOGRAPHIC CASE STUDY IN UNWIMA - Teddy Asmara (Jurnal Dinamika Hukum, 2015)
This research describes repressive legal habitus Unwima community by focusing on the issue of why they create a legal cognition such manner and how to empower them in the public domain when facing a lawsuit in court and examination process in higher education office. The results of the research with ethnographic methods and interpretative analysis, First, that repressive legal habitus is a part of the neo-feudalistic thinking in education management. Second, the empowerment of repressive legal habitus in the public domain potentially generate a legal behavior of impulsive that tends to a manipulative, coercive, veiled, and other immorality practices.Keywords: ethnography, legal habitus, repressive law, neo-feudalistic